2011
DOI: 10.1177/0269216311429042
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of incurable cancer status and health-related quality of life among advanced cancer patients: A prospective cohort study

Abstract: Our findings demonstrate the importance of patients' awareness of disease status to HRQOL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
74
1
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(79 citation statements)
references
References 46 publications
0
74
1
4
Order By: Relevance
“…However, we did not find an association between information provision and illness perceptions for patients with mCRC. In comparison, a recent study showed that patient awareness of incurable disease was associated with improvements in health status, 40 because they were better able to understand and manage their symptoms.…”
Section: Husson Et Al Discussionmentioning
confidence: 97%
“…However, we did not find an association between information provision and illness perceptions for patients with mCRC. In comparison, a recent study showed that patient awareness of incurable disease was associated with improvements in health status, 40 because they were better able to understand and manage their symptoms.…”
Section: Husson Et Al Discussionmentioning
confidence: 97%
“…In a previous study, the all-cause and cancer-specific survival of a cancer-status-aware group was 1.3-fold higher than that of a non-aware group [5]. Additionally, a group of patients who were aware of having incurable cancer showed a higher health-related quality of life than patients who were unaware of that status [6].…”
Section: Introductionmentioning
confidence: 82%
“…Yet, in many cultures, such as in collectivist Asian and Muslim cultures, illness is a shared family affair, and concealing the truth is a common practice, whereas in Western cultures, the disclosure of diagnosis and terminal prognosis is regarded as patient autonomy [8]. Relating to these issues, the prognostic awareness of patients with cancer has generated a growing interest among researchers [9][10][11][12][13]. However, the prevalence of disease prognosis and perception of treatment purpose were inconsistent in these studies.…”
Section: Introductionmentioning
confidence: 99%